Olefin cross-metathesis-based approaches to furans: procedures for the preparation of di- and trisubstituted variants. - Donohoe, T; Bower, J; Basutto, J (2010)
Olefin cross-metathesis (CM)-based protocols enable short, flexible and regiocontrolled access to substituted furan derivatives. Specifically, CM of allylic alcohol and enone components provides γ-hydroxyenone intermediates that are cycloaromatized to the final furan derivatives on exposure to either acid or a discrete Heck arylation step. This latter process concomitantly introduces an extra substituent onto the furan target with complete control of regiochemistry. The methodology described here serves as the basis for developing other CM-based entries to diverse heteroaromatic compounds. This protocol describes in detail the following stages of the furan procedures: (i) the tandem formation and acid-catalyzed cyclization of the γ-hydroxyenone to afford a 2,5-disubstituted furan directly; (ii) CM of an allylic alcohol with an enone to provide an isolated γ-hydroxyenone; and (iii) Heck arylation of this γ-hydroxyenone to afford a 2,3,5-trisubstituted furan. The reaction procedure given for the formation of the 2,5-disubstituted furan (option A) takes ∼26.5 h to complete. The procedure described for the formation of the 2,3,5-trisubstituted furan (option B) takes ∼52.5 h.